172k views
2 votes
Solve x^2 + 5x – 3 = 0 using the quadratic formula.

Solve x^2 + 5x – 3 = 0 using the quadratic formula.-example-1

1 Answer

4 votes

The quadratic formula is:


x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

For a quadratic equation in standard form:


ax^2+bx+c=0

In this case, we have:


\begin{gathered} a=1 \\ b=5 \\ c=-3 \end{gathered}
\begin{gathered} x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ x=\frac{-5\pm\sqrt[]{(5)^2-4(1)(-3)}}{2(1)} \\ x=\frac{-5\pm\sqrt[]{25+12}}{2} \\ x=\frac{-5\pm\sqrt[]{37}}{2} \end{gathered}

The given quadratic equation has two solutions:

• First one


\begin{gathered} x_1=\frac{-5+\sqrt[]{37}}{2} \\ x_1=-(5)/(2)+\frac{\sqrt[]{37}}{2} \end{gathered}

• Second one


\begin{gathered} x_2=\frac{-5-\sqrt[]{37}}{2} \\ x_2=-(5)/(2)-\frac{\sqrt[]{37}}{2} \end{gathered}

Therefore, the solutions of the given quadratic equation are:


$$\boldsymbol{x=-(5)/(2)+\frac{\sqrt[]{37}}{2}}$$,$$\boldsymbol{x=-(5)/(2)-\frac{\sqrt[]{37}}{2}}$$

User Chris Butler
by
5.0k points